PENGARUH IDENTITAS MEREK, CITRA MEREK, DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS PADA KONSUMEN SEPATU NIKE DI JAKARTA - Budihardja, Louis; Sitinjak, Tony (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
Globalization, combined with technology advancements, has allowed the shoe industry to flourish and be appreciated by a global audience. The present shoe industry is also threatened by the quick change in fashion. Nike is an example of one of the world's largest corporations. In a competitive environment, characteristics such as brand identity, brand image, brand trust, and brand loyalty are critical to the company's success. Consumers will remember the identity of the brand if they have a loyal attitude and believe in the goods. This will improve the brand's image and credibility, as well as encourage customers to purchase again. As a result, the authors want to investigate the impact of brand identity, brand image, and brand trust on Nike shoe brand loyalty.